A novel biocompatible polymeric blend for applications requiring high toughness and tailored degradation rate. Issue 10 (4th March 2021) - Heidari, Behzad Shiroud; Chen, Peilin; Ruan, Rui; Davachi, Seyed Mohammad; Al-Salami, Hani; De Juan Pardo, Elena; Zheng, Minghao; Doyle, Barry
Abstract : Finding the right balance in mechanical properties and degradation rate of biodegradable materials for biomedical applications is challenging, not only at the time of implantation but also during biodegradation. Abstract : Finding the right balance in mechanical properties and degradation rate of biodegradable materials for biomedical applications is challenging, not only at the time of implantation but also during biodegradation. For instance, high elongation at break and toughness with a mid-term degradation rate are required for tendon scaffold or suture application, which cannot be found in each alpha polyester individually. Here, we hypothesise that blending semi-crystalline poly( p -dioxanone) (PDO) and poly(lactide- co -caprolactone) (LCL) in a specific composition will enhance the toughness while also enabling tailored degradation times. Hence, blends of PDO and LCL (PDO/LCL) were prepared in varying concentrations and formed into films by solvent casting. We thoroughly characterised the chemical, thermal, morphological, and mechanical properties of the new blends before and during hydrolytic degradation. Cellular performance was determined by seeding mouse fibroblasts onto the samples and culturing for 72 hours, before using proliferation assays and confocal imaging. We found that an increase in LCL content causes a decrease in hydrolytic degradation rate, as indicated by induced crystallinity, surface and bulk erosions, and tensile properties. Interestingly, the noncytotoxic blend containing 30% PDO and 70% LCL (PDO3LCL7) resulted in small PDO droplets uniformly dispersed within the LCL matrix and demonstrated a tailored degradation rate and toughening behaviour with a notable strain-hardening effect reaching 320% elongation at break; over 3 times the elongation of neat LCL. In summary, this work highlights the potential of PDO3LCL7 as a biomaterial for biomedical applications like tendon tissue engineering or high-performance absorbable sutures.